National food policies impacting on food security: The experience of India, a large populated country - S. S. Acharya (The United Nations University World Institute for Development Economics Research (UNU-WIDER), 2006)
India accounts for 16.7 per cent of the world's food consumers. With the exception of China, India's size in terms of food consumers is many times larger than the average size of the rest of the countries. At the time of independence in 1947, India was in the grip of a serious food crisis, which was accentuated by the partition of the country. The demand for food far exceeded supply, food prices were high and more than half of the population living below the poverty line with inadequate purchasing power. With high rates of population growth, the dependence on imported food increased further. However, the situation improved considerably after the mid-1960s, when new agricultural development strategy and food policies were adopted. The production of staple cereals increased substantially, mainly contributed by productivity improvements. The dependence on food imports decreased and the country became a marginal net exporter of cereals. There was also an improvement in physical and economic access of households to cereals and other nutritive food products. The proportion of households reporting hunger went down and the incidence of economic poverty reduced. This paper reviews the Indian approach to tackling the severe problem of food insecurity, which India faced immediately after independence. It reviews the evolution of food policy, the major policy instruments deployed, intervention in food marketing system, and the current status of food security/insecurity. The paper also identifies the lessons emerging from the experience of India. In developing countries characterized by large segments of the rural population dependent on food production for livelihood and by the high incidence of poverty, food insecurity and malnutrition, the strategy to improve food security must encompass programmes to increase food production that combine improved technology transfer, price support to food producers and supply of inputs at reasonable prices to farmers, improvements in food marketing system, employment generation, direct food assistance programmes, and improvement in the access to education and primary health care. – agriculture ; marketing ; subsidies ; food policy ; food security ; distribution ; nutrition ; India
Keywords: Q18; H53; I18; 330; Nahrungsmittelversorgung; Ernährungspolitik; Indien